If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 9z + -1 = 6z + 62 + -4z Reorder the terms: 7 + -1 + 9z = 6z + 62 + -4z Combine like terms: 7 + -1 = 6 6 + 9z = 6z + 62 + -4z Reorder the terms: 6 + 9z = 62 + 6z + -4z Combine like terms: 6z + -4z = 2z 6 + 9z = 62 + 2z Solving 6 + 9z = 62 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. 6 + 9z + -2z = 62 + 2z + -2z Combine like terms: 9z + -2z = 7z 6 + 7z = 62 + 2z + -2z Combine like terms: 2z + -2z = 0 6 + 7z = 62 + 0 6 + 7z = 62 Add '-6' to each side of the equation. 6 + -6 + 7z = 62 + -6 Combine like terms: 6 + -6 = 0 0 + 7z = 62 + -6 7z = 62 + -6 Combine like terms: 62 + -6 = 56 7z = 56 Divide each side by '7'. z = 8 Simplifying z = 8
| .43xb=97.2 | | 7x+9-5(x+1)=5x+6 | | 297=3x^2+6 | | 30t=22t+80 | | (32.453)(34.23+1.17)= | | -2(-3z)=42 | | 3/4x+3=-3 | | y=52 | | z-42/3=22/3 | | 52x= | | 114=(x+7)x(2) | | -10m+2m=13-45 | | 4-3(2a+3)-5=2a+1 | | 114=(x+2)x(7) | | 3t+3t=18-19+7 | | 288=(x+2)x(6) | | 3(6x-12)=2(8x-4) | | 5cosx-2sinx=3 | | r-4=3r-16-r | | -8p+5+9p=7 | | 9m+2n-3m+7n= | | a+4=-7 | | -1+12=5b-4-4b | | f(-3)=6x^2-5x-6 | | 50-3*x=8 | | f(x)=6x^2-5x-6 | | x/2+4=-20 | | 7xy+4yz-8xz-7xy= | | Y=52x | | y-4y=-15 | | 5x+8+x+4=35 | | F(-5)+f(3)= |